The effect of coffee intake towards human body / Noorliza Zainol and Abdul Rahman Ahmad Rozali - Zainol, Noorliza; Ahmad Rozali, Abdul Rahman (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Coffee is the most popular consumed beverages which contain caffeine to boost mental alertness. Morning breakfast with a cup of coffee significantly affects activities of body hormone throughout the day. Excluding coffee from the daily intake could reduce blood pressure, stress reactions and high blood pressure (Fan, L.; Zhang, H.M. and Cai, J., 2018; James D., 2002). Besides, it also may potentially affect disease risks (Basar, B. G. and Sanlier, N., 2017; Taylor and Adams, 2007). Caffeine effects from coffee differs from one person to another depending on various factors. This include consumption pattern, serving size, and coffee type.